Recent Applications of Polymer Blends in Gas Separation Membranes. Issue 11 (11th October 2013) - Mannan, H. A.; Mukhtar, H.; Murugesan, T.; Nasir, R.; Mohshim, D. F.; Mushtaq, A.
Abstract Polymeric membranes are extensively used for gas separations but their performance is limited by the upper bound trade‐off discovered by Robeson in 1991. Among the attractive modifications available to increase the performance of polymeric membranes, polymer blending is a unique technique because it offers a time‐ and cost‐effective method of tuning the properties of membranes. A variety of polymer blends has been explored in recent years. The application of polymer blends in gas separation membranes is described by critically analyzing the performance of polymer blend membranes. Polymer blend membranes of different polymer pairs are reviewed and evaluated in terms of phase behavior, permeability, and selectivity.